Brief analysis of the development characteristics and deformation mechanism of ground fissures on the MH Highway in the Ethiopian Rift Valley - Liu, Weimin; Xu, Cheng; Huang, Xiaonian (Frontiers in Earth Science, 2023)
Ground fissures are widely developed in the Ethiopian Rift Valley, posing a major threat to the construction of the proposed MH (Modjo-Hawassa) highway. The development characteristics, distribution and communication law of ground fissures along the highway are studied by the comprehensive investigation method and technology. On this base, the deformation mechanism and evolution of ground fissures are analyzed, which can provid geological support for the prevention and control of highway cracks in the area where ground fissures are developed.